![image](https://tex.z-dn.net/?f=27%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%2B9%5E%7B-1%7D%3D%283%5E3%29%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%2B%283%5E2%29%5E%7B-1%7D%3D3%5E2%2B3%5E%7B-2%7D%3D9%2B%5Cfrac%7B1%7D%7B9%7D%3D9%5Cfrac%7B1%7D%7B9%7D%5C%5C%5C%5C%5C%5C%5Csqrt%7Bx%2B4%7D%3D7%2C%5C%3B+%5C%3B+x%3E-4%5C%5C%5C%5Cx%2B4%3D49%5C%5C%5C%5Cx%3D45%5C%5C%5C%5C%5C%5C%5Cfrac%7Blog_713%7D%7Blog_%7B49%7D13%7D%3D%5Cfrac%7Blog_713%7D%7Blog_%7B7%5E2%7D13%7D%3D%5Cfrac%7Blog_713%7D%7B%5Cfrac%7B1%7D%7B2%7Dlog_713%7D%3D2)
-4\\\\x+4=49\\\\x=45\\\\\\\frac{log_713}{log_{49}13}=\frac{log_713}{log_{7^2}13}=\frac{log_713}{\frac{1}{2}log_713}=2" alt="27^{\frac{2}{3}}+9^{-1}=(3^3)^{\frac{2}{3}}+(3^2)^{-1}=3^2+3^{-2}=9+\frac{1}{9}=9\frac{1}{9}\\\\\\\sqrt{x+4}=7,\; \; x>-4\\\\x+4=49\\\\x=45\\\\\\\frac{log_713}{log_{49}13}=\frac{log_713}{log_{7^2}13}=\frac{log_713}{\frac{1}{2}log_713}=2" align="absmiddle" class="latex-formula">